Claims on Sri Lankan Food Labels: A Comparative Legal Analysis with Selected Jurisdictions - Charith Amidha Hettiarachchi; Mahendra Arnold; Niroshika Liyana Muhandiram; Jon Wardle (The Open University of Sri Lanka, 2020)
Claims on labels are one of major marketing strategies in the food industry. Health of consumers may be affected by inaccurate and misleading claims and therefore, such claims need to be regulated by state legislation. The Food (Labelling and Advertising) Regulations, 2005 made under the Food Act of 1980 is the main law governing food labelling claims in Sri Lanka. This study is a desk review which analyses the relevant regulations in the Food (Labelling and Advertising) Regulations, 2005. The study further critiques the existing regulations and compares with international standards (Codex Alimentarius) and regulations in developed countries such as Australia which have a broad local and international food market with modern technology. The objective of the study is to identify the scope of the 'claim' and its current legislative pitfalls under the existing Sri Lankan legal domain together with its permeability and restrictions. This study finds that the regulations on claims are not precisely structured and less strong in Sri Lanka. The scope of the definition of 'claim' is vague. Only limited types of claims are stated within the legislation and are often wrongly classified. Certain claim types are not defined at all in the Sri Lankan regulations. Therefore, this study suggests that in order to improve public health, future amendments to the existing regulations are necessary with broader, stronger and clear regulations.